The Pituitary-Adrenal Response to Paradoxical Sleep Deprivation Is Similar to a Psychological Stressor, Whereas the Hypothalamic Response Is Unique - Moraes, Danilo A.; Machado, Ricardo B.; Koban, Michael; Hoffman, Gloria E.; Suchecki, Deborah (Frontiers in Endocrinology, 2022)
Stressors of different natures induce activation of the hypothalamic-pituitary-adrenal (HPA) axis at different magnitudes. Moreover, the HPA axis response to repeated exposure is usually distinct from that elicited by a single session. Paradoxical sleep deprivation (PSD) augments ACTH and corticosterone (CORT) levels, but the nature of this stimulus is not yet defined. The purpose of the present study was to qualitatively compare the stress response of animals submitted to PSD to that of rats exposed once or four times to cold, as a physiological stress, movement restraint (RST) as a mixed stressor and predator odour (PRED) as the psychological stressor, whilst animals were submitted for 1 or 4 days to PSD and respective control groups. None of the stressors altered corticotropin releasing factor immunoreactivity in the paraventricular nucleus of the hypothalamus (PVN), median eminence (ME) or central amygdala, compared to control groups, whereas vasopressin immunoreactivity in PSD animals was decreased in the PVN and increased in the ME, indicating augmented activity of this system. ACTH levels were higher after repeated stress or prolonged PSD than after single- or 1 day-exposure and control groups, whereas the CORT response was habituated by repeated stress, but not by 4-days PSD. This dissociation resulted in changes in the CORT:ACTH ratio, with repeated cold and RST decreasing the ratio compared to single exposure, but no change was seen in PRED and PSD groups. Comparing the magnitude and pattern of pituitary-adrenal response to the different stressors, PSD-induced responses were closer to that shown by PRED-exposed rats. In contrast, the hypothalamic response of PSD-exposed rats was unique, inasmuch as this was the only stressor which increased the activity of the vasopressin system. In conclusion, we propose that the pituitary-adrenal response to PSD is similar to that induced by a psychological stressor.